APPLICATION OF PRINCIPLE FULL DISCLOSURE AND LEGAL PROTECTION FOR INVESTOR DUE TO MARKET MANIPULATION OF SHAREPRICES BY ISSUERS IN CAPITAL MARKET - Pohan, Ghiffary Akmal Alija; Priyono, FX. Joko; Priyono, Ery Agus (CREPIDO, 2023)
Capital market plays an essential role in economic activity, particularly in the allocation of public money which is can’t be separated from the role of investor and issuer as well as the implementation of capital market, stipulated in the Capital Market Law No. 8 Year 1995. The transaction mechanism between the investor and the issuer themselves known as the Initial Public Offering (IPO) which furtherly understood as the process of selling securities from the issuers to investors. Hence, in the running of capital market itself there were found such a violation in the principle of full disclosure, also, the market manipulation that obviously undertook in the IPO that would obviously causes several losses for the investor rights. The research method was carried out using a judicial normative legal approach, in which, solely through the examination of library materials or secondary data. All the legal materials obtained would be analyzed using a logical/systematical interpretation referring to the relatable laws and regulations, also supported from the judge decision that strengthened the legal issue which further explaining the research’s result and discussion. It is clear that the Issuer responsibility would be served under the supervision of the Financial Services Authority (OJK) that would undertook either the preventive or the repressive action toward every crimes formed by the issuer. So does in the market manipulation cases, there would be imposing sanctions contained in the Capital Market Law in the form of criminal and administrative sanctions which were given intentionally of having a deterrent effect and providing legal certainty upon the Capital Market Law.